2018
DOI: 10.3390/w10101385
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Arsenic from Water with Non-Thermal Plasma (NTP), Coagulation and Membrane Filtration

Abstract: Arsenic in drinking water resources and, especially, in groundwater, represents a severe health problem for millions of people in affected regions. This paper investigates a removal technology combining non-thermal plasma at a reaction time of 30 min, which has improved the downstream coagulation and the filtration efficiency. The results show removal rates of total arsenic over 98%. In addition, WHO limits of less than 10 g / L could be achieved in both batch and continuous set-ups. A difference in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…A series of batch sorption experiments were carried out to explore the effect of SCB-BC, RH-BC, Th/SCB-BC, and Th/RH-BC under varying pH (3)(4)(5)(6)(7)(8)(9)(10), contact time (0-24 hr), sorbent dose (1-16 mg L − 1 ) and initial As(III) concentration (0.05-10 mg L − 1 ) under laboratory conditions. In 50 mL plastic centrifuge tubes, sorption experiments were performed using 0.01 M NaCl solution as background electrolyte.…”
Section: Batch Sorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of batch sorption experiments were carried out to explore the effect of SCB-BC, RH-BC, Th/SCB-BC, and Th/RH-BC under varying pH (3)(4)(5)(6)(7)(8)(9)(10), contact time (0-24 hr), sorbent dose (1-16 mg L − 1 ) and initial As(III) concentration (0.05-10 mg L − 1 ) under laboratory conditions. In 50 mL plastic centrifuge tubes, sorption experiments were performed using 0.01 M NaCl solution as background electrolyte.…”
Section: Batch Sorption Experimentsmentioning
confidence: 99%
“…Various conventional and traditional techniques are available to remediate As from As-contaminated water including ion exchange, electrochemical, precipitation, membrane separation and solvent extraction (Chen et al 2023, Back et al 2018, Chiban et al 2012). Most of these techniques incur substantial capital and operational costs, making them challenging for successful execution in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the best protocol enhancing seed vigor and germination performance of maize [16]. It has been found that 98% of arsenic from ground water has been removed by non-thermal plasma treated for 30 min and after coagulation and membrane filtration [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The species of As in the groundwater contribute to the exposure risk, and the order of decreasing toxicity is R 3 As > H 3 AsO 3 > H 3 AsO 4 > R 4 As + > As 0 , where R is a proton or an alkyl group [3,4]. Several As removal technologies have been tested and implemented, such as adsorption (iron fillings, lignite, manganese ore), electrocoagulation [5], and filtration (modified ultrafiltration and nanofiltration) [6]. There is still much to cover when it comes to As pollution mapping, As remediation technology implementation, and research-driven policy-making in the country [7].…”
Section: Introductionmentioning
confidence: 99%